P146 Can masks protect you from air pollution?. (15th November 2017) - Liu, NM; Wan, T; Russell-Jones, EC; Grigg, J
Abstract : Introduction: Inhalation of diesel soot (black carbon) is associated with respiratory morbidity and mortality. Numerous facemasks that claim to reduce inhaled dose are available commercially, often aimed at the cycling community. To date it remains unclear whether these actually reduce exposure. In this study we sought to assess the effectiveness of some of masks available in the UK. Methods: We chose to assess 5 facemasks; i) Totobobo, ii) FFP3 industrial, iii) surgical, iv) Respro City Anti-Pollution, and v) Dettol Protect+. Masks was placed using an air tight seal at one end of a spacer chamber (Aerochamber). Researchers breathed through the spacer, and air within the spacer chamber sampled by an aethalometer (MicroAeth AE51) every 30 s. For each 30 s period, spacer black carbon (ng/m 3 ) was compared with ambient black carbon. Each mask was tested for at least 15 min on the pavement of busy roads in Marylebone and Whitechapel. Data are expressed as; i) mean of difference (±SEM) between ambient and spacer air black carbon and ii) as percentage reduction of mean black carbon. Data are compared by paired T-test. Results: Totobobo mask was the most effective with a mean difference of −2022 ng/m 3 (±175 ng/m 3, p<0.0001; 71% reduction, figure 1 ). The FFP3 mask had a mean difference of −1613 ng/m 3 (±204 ng/m 3, p<0.0001; 44.2% reduction); Dettol Protect+mask with the USB ventilator on had a mean difference of −331.9 ng/m 3 (±74.89 ng/m 3, p<0.0001; 42% reduction). With the ventilator off, the Dettol Protect+had a mean difference of −530 ng/m 3 (±147 ng/m 3, p<0.01; 42% reduction). The Repro City had a mean difference of −261 ng/m 3 (±113 ng/m 3, p<0.05; 30% reduction), and the surgical mask had a trend for increased spacer black carbon +2252 ng/m 3 (±1071 ng/m 3, p=0.05). Conclusions: Four of the five masks tested reduced spacer black carbon. The USB chargeable fan of the Dettol Protect+mask added minimal benefit. Why the surgical mask did not reduce black carbon is unclear but we speculate that condensation from exhalation impaired particle filtering.